Hubungan Tipe Kepribadian Mahasiswa Dengan Prestasi Akademik Pada Mahasiswa Fakultas Kedokteran Universitas Lampung Angkatan 2015 - Oktafany; Sofyan Musyabiq; Nindya Augesti (CV. Jasa Sukses Abadi, 2021)
Every person has their own characteristics that affect their behavior in learning process. The particular characteristics of an individual are called personalities. Becoming a professional doctor is not only seen from the knowledge and skills, but also in terms of personality. There are two personality types in this study, namely type A personality and type B personality. The personality type of a student determine academic achievement that also influence their service as a doctor in the future. The purpose of this study was to determine the relationship of personality types to academic achievement in students class of 2015 in Medical Faculty Lampung University. This study used an analytical research method with a cross sectional study approach. Sample of this study consist of 136 students from the class of 2015 determined by total sampling. This study used a Personality Type Friedman and Rosenman questionnaire and Grade Point Avarage (GPA) dataThe data were analized by using Chi-Square test. This study showed that the type A personality is 53.7% and 51.5% are having very good GPA score. Acording to chi-square analitic, there was a significant relationship between type of personality and GPA score of medical student of Lampung University class of 2015 with p value 0.001.